Chondral Delamination of Fresh Osteochondral Allografts after Implantation in the Knee: A Matched Cohort Analysis. (October 2019) - Rauck, Ryan C.; Wang, Dean; Tao, Matthew; Williams, Riley J.
Introduction: Delamination of the chondral surface of an osteochondral allograft (OCA) from the underlying cancellous bone has been described as a mode of failure after implantation in the knee. Our hypothesis was that increased storage time of the OCA is associated with increased risk of graft delamination after implantation. Methods: Prospective data on 13 patients with evidence of OCA delamination identified on magnetic resonance imaging or during subsequent surgery from 2000 to 2015 were reviewed. A cohort of 33 patients without evidence of graft delamination were then matched to the delamination group based on recipient age, sex, body mass index (BMI), and chondral defect location. The matched cohort size was established based on a power calculation for determining differences in OCA storage times. All patients had a minimum 2-year follow-up. Results: There was no difference in donor age, donor sex, and graft storage time between groups (30 vs. 31 days, P = 0.78). There were no differences between number of previous ipsilateral knee surgeries (1.8 vs. 0.84, P = 0.26), BMI (26.8 vs. 25.0 kg/m 2, P = 0.31), total chondral defect size (6.5 vs. 5.8 cm 2, P = 0.41) or preoperative Marx activity scores between groups. Conclusion: There is no association between OCA storage time, activity level scores, or number of previous ipsilateral knee surgeries and graft delamination in our patient population. Further work is needed to identify the etiology for this mode of failure of OCAs.